Present and Future of Internationalization of Higher Education: Insights from the Sixth IAU Global Survey - Marinoni, Giorgio; van’t Land, Hilligje; de Wit, Hans (International Higher Education, 2024)
The sixth IAU Global Survey comes on time to draw a holistic picture of internationalization of higher education around the world, to capture key changes over the period of 2018-2022, including the COVID-19 pandemic, and to give hints on how internationalization could evolve in the future. Key findings of this survey presented provide a tool to enhance quality, inclusion, equity, and social responsibility through internationalization.